Systematic Review of Guidelines for the Management of Asymptomatic and Symptomatic Carotid Stenosis. Issue 11 (November 2015) - Abbott, Anne L.; Paraskevas, Kosmas I.; Kakkos, Stavros K.; Golledge, Jonathan; Eckstein, Hans-Henning; Diaz-Sandoval, Larry J.; Cao, Longxing; Fu, Qiang; Wijeratne, Tissa; Leung, Thomas W.; Montero-Baker, Miguel; Lee, Byung-Chul; et al.
Abstract : Background and Purpose—: We systematically compared and appraised contemporary guidelines on management of asymptomatic and symptomatic carotid artery stenosis. Methods—: We systematically searched for guideline recommendations on carotid endarterectomy (CEA) or carotid angioplasty/stenting (CAS) published in any language between January 1, 2008, and January 28, 2015. Only the latest guideline per writing group was selected. Each guideline was analyzed independently by 2 to 6 authors to determine clinical scenarios covered, recommendations given, and scientific evidence used. Results—: Thirty-four eligible guidelines were identified from 23 different regions/countries in 6 languages. Of 28 guidelines with asymptomatic carotid artery stenosis procedural recommendations, 24 (86%) endorsed CEA (recommended it should or may be provided) for ≈50% to 99% average-surgical-risk asymptomatic carotid artery stenosis, 17 (61%) endorsed CAS, 8 (29%) opposed CAS, and 1 (4%) endorsed medical treatment alone. For asymptomatic carotid artery stenosis patients considered high-CEA-risk because of comorbidities, vascular anatomy, or undefined reasons, CAS was endorsed in 13 guidelines (46%). Thirty-one of 33 guidelines (94%) with symptomatic carotid artery stenosis procedural recommendations endorsed CEA for patients with ≈50% to 99% average-CEA-risk symptomatic carotid artery stenosis, 19 (58%) endorsed CAS and 9 (27%) opposed CAS. For high-CEA-risk symptomatic carotid artery stenosis because of comorbidities, vascular anatomy, or undefined reasons, CAS was endorsed in 27 guidelines (82%). Guideline procedural recommendations were based only on results of trials in which patients were randomized 12 to 34 years ago, rarely reflected medical treatment improvements and often understated potential CAS hazards. Qualifying terminology summarizing recommendations or evidence lacked standardization, impeding guideline interpretation, and comparison. Conclusions—: This systematic review has identified many opportunities to modernize and otherwise improve carotid stenosis management guidelines.